Relocation Preferences of Street Vendors at Pasar Sore Tanjung Selor: An Analysis of Environmental and Economic Aspects - Kartini Kartini; Dedy Rahmatullah; Silvia Margaret; Bernadeth Yosephine Priskilla Br Simangunsong; Rizky Agusriyanti Irna (Journal of Economic Education and Entrepreneurship Studies, 2026)
This study examines the relocation preferences of street vendors (Pedagang Kaki Lima, PKL) at Pasar Sore Tanjung Selor, with a focus on environmental and economic aspects. The research employed a mixed-methods approach, combining quantitative surveys of 37 street vendors and qualitative interviews with consumers, community leaders, and local government officials. Quantitative data were analyzed using Likert scales to measure perceptions of environmental conditions, comfort, safety, and economic opportunities at two potential relocation sites: Pasar Induk and Pasar Subuh. The findings indicate that both environmental and economic aspects were rated positively, with total scores of 74% and 72%, respectively. Overall, 81% of respondents preferred Pasar Subuh as the relocation site due to its accessibility, comfort, and economic potential, while 19% favored Pasar Induk for compliance with government regulations and space management. The study highlights the importance of considering both environmental and economic factors in relocation planning and provides practical insights for policymakers aiming to improve the organization and sustainability of local markets.